Allocating greenhouse gas emissions among countries with mobile populations - Michael Hoel (University of Oslo, Department of Economics, 2001)
In the negotiations towards an agreement to reduce greenhouse gas emissions, one of the issues negotiated will be the allocation of emissions (or tradable emission permits) between countries. In most analyses and policy discussions, it is usually taken for granted that each country would like their own share of the total permitted emissions to be as large as possible. The paper demonstrates that if there is population mobility between a group of countries, this might not be true. If there is a perfectly homogeneous and mobile population in the countries considered, all these countries have a common interest in a particular allocation of emission quotas. In the more realistic case of population heterogeneity, there will typically be an interest conflict among countries regarding the allocation of emission quotas. However, it need no longer be true that each country is better off the larger its share of the total number of emission quotas.
Keywords: F02; F22; H70; Q20; 330; Climate agreements; greenhouse gases; population mobility; Klimaveränderung; Internationale Umweltpolitik; Klimaschutz; Internationale Wanderung; Theorie